Facilitation of lithium polysulfides adsorption by nitrogen doped carbon nanofibers with 3D interconnected pore structures for high-stable lithium-sulfur batteries. (10th August 2018) - Liang, Yueyao; Deng, Nanping; Ju, Jingge; Zhou, Xinghai; Yan, Jing; Zhong, Chongli; Kang, Weimin; Cheng, Bowen
Abstract: Lithium-sulfur battery is one of the most prospective chemistries in secondary energy storage field due to its high energy density and theoretical capacity, but the rapid decay of capacity is still a huge challenge. Herein, we reported an ingenious design of nitrogen doped carbon nanofibers with honeycomb-like porous structure for the cathode of lithium-sulfur battery which can effectively suppress the "shuttle effect". The special porous material with three dimensional (3D) interconnected pore structure is beneficial to enhance the adsorption of lithium polysulfides and accommodate the volume expansion of active materials. In addition, the doped nitrogen can not only improve the conductivity of cathode, but also form a strong interfacial interaction to trap lithium polysulfides. Therefore, the battery with the cathode exhibited a high reversible discharge capacity of 1093.9 mAh g −1 and good capacity retention of 76.0% after 300 cycles at 0.5C rate. After acidification, the cycling performance of the cathode could achieve upon 300 cycles with a very low decay rate of 0.027% at 0.5C.